Photosensitive glass and production method therefor
Patent Information
- Application Number
- JP2023124791
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0009】 本発明の一態様によれば、感光性ガラスにおいて露光部と未露光部における結晶析出温度に明確な差を設けることができる。例えば同一組成の感光性ガラスであっても上記結晶析出温度差を広げることができる。あるいは、結晶析出温度差が狭くなるようなガラス組成であっても、実用上許容される範囲にまで上記結晶析出温度差を広げることができる。そのため、露光及び熱処理した際に、精度良くパターン加工が可能な感光性ガラス、及びその製造方法を提供できる。
Smart Images

Figure 2025021075000002 
Figure 2025021075000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a photosensitive glass and a method for producing the same. [Background technology]
[0002] Photosensitive glass is glass whose glass structure changes in the exposed areas when exposed to light and heat treatment are combined. Specifically, by applying heat to glass exposed to short-wavelength radiation such as ultraviolet light, Ag colloids are formed in the exposed areas, and the Ag colloids then act as nuclei for the precipitation of fine crystals, changing the color, refractive index, chemical durability, and glass strength of the exposed areas (see, for example, Patent Document 1).
[0003] Photosensitive glass includes those that precipitate NaF (sodium fluoride) crystals as fine crystals, and those that precipitate Li2SiO3 / Li2Si2O5 (lithium silicate system). Photosensitive glass with NaF crystal precipitation is used in volume holographic gratings, while photosensitive glass with lithium silicate crystal precipitation is used in circuit boards for high-frequency applications. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-36200 A Summary of the Invention [Problem to be solved by the invention]
[0005] Photosensitive glass requires the precipitation of crystals in a fine pattern depending on the application, so it is required that the pattern shape can be formed with high precision and that the properties due to the precipitation of crystals be imparted sufficiently.
[0006] SUMMARY OF THE INVENTION It is therefore an object of the present invention to provide a photosensitive glass that can be patterned with high precision when exposed to light and heat treated. [Means for solving the problem]
[0007] In order to obtain a photosensitive glass that can be patterned with high precision after exposure and heat treatment, it is important to ensure a clear difference in the crystal precipitation temperature between the exposed and unexposed areas. While it is generally known that the difference in crystal precipitation temperature is affected by the glass composition, the present inventors have newly discovered that controlling the β-OH value in the photosensitive glass is also effective in adjusting the difference in crystal precipitation temperature, and have completed the present invention.
[0008] That is, one aspect of the present invention relates to a photosensitive glass having a β-OH value of 0.20 / mm or less. Another aspect of the present invention relates to a method for producing photosensitive glass, comprising heating a glass raw material containing a photosensitizer component to obtain molten glass, molding the molten glass into a desired shape, and slowly cooling the molded glass, wherein the method further comprises reducing the β-OH value of the photosensitive glass. [Effects of the Invention]
[0009] According to one aspect of the present invention, a clear difference in crystal precipitation temperature can be established between exposed and unexposed areas of a photosensitive glass. For example, even for photosensitive glasses of the same composition, the difference in crystal precipitation temperature can be widened. Alternatively, even for glass compositions that narrow the difference in crystal precipitation temperature, the difference in crystal precipitation temperature can be widened to a practically acceptable range. Therefore, a photosensitive glass that can be patterned with high precision when exposed and heat-treated, and a method for manufacturing the same, can be provided. [Brief explanation of the drawings]
[0010] [Figure 1]1(a) and 1(b) are micrographs of the micro-machined glass of the Examples after micro-machining, where 1(a) is a micrograph of the micro-machined glass of Example 14 after micro-machining, and 1(b) is a micrograph of the micro-machined glass of Example 15 after micro-machining. DETAILED DESCRIPTION OF THE INVENTION
[0011] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be implemented in any modified form without departing from the gist of the present invention. In this specification, unless otherwise specified, the use of "to" to indicate a range of values means that the values before and after it are included as the lower and upper limits.
[0012] In this specification, "photosensitive glass" refers to glass in which metal colloids are generated in the glass by exposure to light and heat treatment, and further crystals are precipitated. More specifically, "photosensitive glass" refers to glass in which a chemical reaction occurs upon exposure to light, and the Ag contained in the photosensitive glass is precipitated. + The ions become metal atoms by receiving electrons. The photosensitive glass is then heat-treated to form silver colloids, and by further increasing the temperature and heat treatment, crystals are precipitated using the silver colloids as nuclei.
[0013] One embodiment of the photosensitive glass of the present invention is a photosensitive glass in which NaF crystals precipitate as the primary crystals upon exposure and heat treatment. Because the refractive index of the glass changes in the region where NaF crystals precipitate, such glass can be suitably used, for example, for volume holographic diffraction gratings. In this specification, the term "primary crystals" refers to the crystals that precipitate in the largest amount among the crystals precipitated upon exposure and heat treatment. In this specification, photosensitive glass in which NaF crystals are precipitated as the main crystals upon exposure and heat treatment is referred to as "refractive index changing glass."
[0014] Another embodiment of the photosensitive glass of the present invention is a photosensitive glass in which lithium silicate crystals such as Li2SiO3 crystals and Li2Si2O5 crystals are precipitated as the main crystals by exposure to light and heat treatment. In photosensitive glass in which lithium silicate crystals are precipitated, the crystals have very high solubility in HF, so the exposed portions can be selectively removed by HF etching, thereby enabling the formation of fine patterns. In this specification, photosensitive glass in which lithium silicate crystals are precipitated as the main crystals by exposure and heat treatment is referred to as "microfabricated glass."
[0015] In this specification, the terms "photosensitive glass of the present invention" and "photosensitive glass according to this embodiment" include refractive index change glass and microfabricated glass.
[0016] The NaF crystals and lithium silicate crystals can be identified by, for example, X-ray diffraction (XRD) measurement. Specifically, they can be identified by measuring by XRD using CuKα radiation at 2θ=10 to 90° and comparing the obtained diffraction peaks with the Cambridge Structural Database (CSD) or the Inorganic Crystal Structure Database (ICSD).
[0017] <Photosensitive glass> The photosensitive glass according to this embodiment is characterized in that the β-OH value is 0.20 / mm or less. The β-OH value refers to the absorbance due to hydroxyl groups. Therefore, by evaluating the β-OH value, the content of water (and / or hydroxide ions, hereinafter simply referred to as "water") in glass can be evaluated. In other words, glass with a high β-OH value means that the water content in the glass is high. In this specification, the β-OH value is calculated using the following formula. β-OH value ( / mm) = (3570 cm -1 Absorbance of -3845cm -1 absorbance) / t Here, t represents the thickness (mm) of the photosensitive glass, and the higher the β-OH value, the higher the water content in the glass. The absorbance can be measured, for example, by Fourier transform infrared spectroscopy.
[0018] The inventors have discovered that the difference in crystal precipitation temperature between unexposed and exposed areas can be adjusted by controlling the β-OH value of the photosensitive glass. By sufficiently increasing the difference in crystal precipitation temperature between unexposed and exposed areas, problems such as crystal precipitation in unnecessary areas can be avoided, allowing for the formation of fine patterns with high precision. The following is thought to be the reason why the difference in crystal precipitation temperature can be controlled by adjusting the β-OH value of the photosensitive glass.
[0019] First, we consider the effect of β-OH on the photosensitive glass before phototreatment, that is, the effect of β-OH on the crystal precipitation characteristics of the photosensitive glass itself. It is presumed that the presence of OH groups in the glass disrupts the Si-O-Si network, lowering the energy barrier required for crystal precipitation from the glass and lowering the crystal precipitation temperature of the glass itself. Another factor is the effect of β-OH on photosensitive glass after phototreatment. After phototreatment, Ag colloids form in the exposed areas of photosensitive glass, which act as crystal nuclei, lowering the energy barrier for crystal precipitation and enabling selective crystal precipitation. Because the resulting decrease in crystal precipitation temperature is greater than the effect caused by β-OH, the crystal precipitation temperature after phototreatment is independent of the amount of β-OH. Therefore, it is speculated that the difference in crystal precipitation temperature between with and without phototreatment will decrease as the amount of β-OH increases and increase as the amount of β-OH decreases. The photosensitive glass of this embodiment is not limited to the above-described mechanism of action.
[0020] In this embodiment, if the β-OH value is 0.20 / mm or less, the difference in crystal precipitation temperature between the unexposed and exposed areas can be made sufficiently large, allowing for the formation of fine patterns with high precision. The β-OH value of the photosensitive glass according to this embodiment is preferably 0.15 / mm or less, more preferably 0.10 / mm or less, even more preferably 0.080 / mm or less, particularly preferably 0.060 / mm or less, and most preferably 0.050 / mm or less. In addition, from the viewpoint of the effectiveness of the β-OH reduction measures, the β-OH value is preferably 0.005 / mm or more.
[0021] The β-OH value can be adjusted, for example, by the melting temperature, melting time, type of raw material, etc. of the glass raw materials during glass production. Specifically, it can be adjusted by the method described later in <Production method of photosensitive glass>.
[0022] The photosensitive glass according to this embodiment has an integrated light intensity of 2 J / cm at wavelengths of 280 to 360 nm. 2 The difference between the crystal precipitation temperature after exposure and the crystal precipitation temperature before exposure (hereinafter referred to as "crystal precipitation temperature difference") is preferably 10°C or more. If the crystallization temperature difference is 10°C or more, the difference in crystallization temperature between the unexposed and exposed areas can be made sufficiently large, thereby avoiding problems such as crystallization in unnecessary areas and enabling pattern processing with high precision. The crystallization temperature difference is more preferably 12°C or more, even more preferably 14°C or more, even more preferably 16°C or more, particularly preferably 18°C or more, and even more preferably 20°C or more. Furthermore, since the greater the crystallization temperature difference, the better, the upper limit is not particularly limited, but is, for example, 50°C or less.
[0023] The crystallization temperature can be measured by, for example, differential thermal analysis or XRD. More specifically, the crystal precipitation temperature of the refractive index-changing glass can be calculated by differential thermal analysis (e.g., Thermoplus TG8120 manufactured by RIGAKU Corporation) and differential scanning calorimetry (e.g., ThermoPlusEVO2 DSC8271 manufactured by RIGAKU Corporation). In this case, with a sample weight of 30 to 60 mg and a heating rate of 10°C / min, the crystal precipitation temperature is the extrapolated temperature of the inflection point at the start of heat generation for the exothermic peak resulting from crystal precipitation under constant heating rate heating. The extrapolated temperature is the temperature at the intersection of an extension of the portion without heat change before heat generation and an extension of the point where the gradient of the heat change after the start of heat generation is maximum.
[0024] The crystallization temperature of the micro-fabricated glass may be calculated by differential thermal analysis and differential scanning calorimetry, as with the refractive index-changing glass. If the crystallization temperature of the micro-fabricated glass cannot be measured by differential thermal analysis and differential scanning calorimetry, the glass is heated at multiple constant temperatures and subjected to X-ray diffraction spectroscopy (e.g., Rigaku's SmartLab X-ray Diffraction Meter), and the temperature at which a diffraction peak derived from Li2SiO3 crystals appears is taken as the crystallization temperature.
[0025] Furthermore, the exposure can be carried out using a high-pressure mercury lamp (e.g., USHIO INC.'s ultra-high pressure mercury lamp USH-250BY) or a photochemical mercury lamp (e.g., Toshiba INC.'s H-400P) based on the UV irradiance measured using an ultraviolet integrating actinometer (e.g., USHIO INC.'s UIT-250) and a photodetector (e.g., USHIO INC.'s UVD-S313 (sensitivity wavelength 280 to 360 nm)).
[0026] (Glass composition) Next, the composition range of each component that may be contained in the photosensitive glass according to this embodiment will be described in detail. When the composition range of each component is expressed as % or ppm, it means percentage by mass and ppm by mass, respectively, unless otherwise specified. Furthermore, the phrase "substantially free" of each component means that it is not contained except as unavoidable impurities mixed in from raw materials, etc., that is, it is not intentionally contained.
[0027] The photosensitive glass according to this embodiment preferably contains 0.001 to 5% Ag2O in mass percentage. Ag2O is a photosensitizer component that serves as the starting point for crystal growth, i.e., the nucleus source, for selectively crystallizing the exposed portions. When the photosensitive glass of this embodiment contains 0.001% or more of Ag2O, the exposed portions can be selectively crystallized. The Ag2O content is preferably 0.005% or more, more preferably 0.008% or more, even more preferably 0.01% or more, particularly preferably 0.012% or more, even more preferably 0.014% or more, and most preferably 0.015% or more. Furthermore, in the photosensitive glass according to this embodiment, the Ag2O content is preferably 5% or less. By setting the Ag2O content to 5% or less, it is possible to prevent Ag2O from remaining undissolved in the glass. Furthermore, it is possible to reduce the burden on the melting equipment. The Ag2O content is more preferably 4% or less, even more preferably 3.5% or less, even more preferably 3% or less, particularly preferably 2.5% or less, even more preferably 2% or less, even more preferably 1% or less, and most preferably 0.5% or less.
[0028] The photosensitive glass according to this embodiment preferably contains CeO2 in an amount of 0.001 to 5% by mass percentage. CeO2 is an optical sensitizer, which makes materials that are only sensitive to high-energy rays such as X-rays sensitive to ultraviolet rays. In addition, it emits electrons when exposed to ultraviolet light, and converts them into Ag + It plays a role in supplying ions. The photosensitive glass according to this embodiment contains 0.001% or more of CeO2, thereby improving sensitivity to exposure to light. The CeO2 content is preferably 0.003% or more, more preferably 0.005% or more, even more preferably 0.01% or more, particularly preferably 0.013% or more, even more preferably 0.015% or more, and most preferably 0.02% or more. Furthermore, in the photosensitive glass according to this embodiment, the CeO2 content is preferably 5% or less. By setting the CeO2 content to 5% or less, the sensitivity to exposure is not too high, and problems such as exposure of unnecessary areas can be avoided, thereby improving pattern accuracy. The CeO2 content is more preferably 4% or less, even more preferably 3.5% or less, even more preferably 3% or less, particularly preferably 2.5% or less, even more preferably 2% or less, even more preferably 1% or less, and most preferably 0.5% or less.
[0029] The photosensitive glass according to this embodiment has, in mass percentage, SiO2: 20~80% Al2O3: 1-20% B2O3: 0-20% Li2O: 0-20% Na2O: 0-20% K2O: 0-20% ZnO: 1 to 20% F: 0-5% Br: 0-5% Ag2O: 0.001~0.5% CeO2: 0.001-0.5% Sb2O3: 0-1.0% SnO2: 0-1.0% It is preferred that the compound contains: The preferred composition ranges of each component in the photosensitive glass according to this embodiment will be described below.
[0030] SiO2 is a component that forms the glass skeleton through a network structure, enhances acid resistance and water resistance, and stabilizes the glass. In microfabricated glass, it is a component that forms and precipitates Li2SiO3 crystals as a crystalline phase. In the photosensitive glass of this embodiment, the SiO2 content is preferably 20 to 80%. An SiO2 content of 20% or more stabilizes the glass, and also facilitates the stabilization of the precipitated crystalline phase of crystallized glass. In the photosensitive glass of this embodiment, the SiO2 content is more preferably 30% or more, even more preferably 40% or more, even more preferably 50% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 70% or more. Furthermore, when the SiO2 content is 80% or less, the glass raw material is easily melted and formed. The SiO2 content is more preferably 79% or less, even more preferably 78% or less, even more preferably 77% or less, particularly preferably 76% or less, and most preferably 75% or less.
[0031] In both the refractive index changing glass and the microfabricated glass, which are specific embodiments of the photosensitive glass of the present invention, the preferred range of the SiO2 content is the same as above.
[0032] Al2O3 is a component that is effective in improving acid resistance, improving Young's modulus, suppressing phase separation of glass, and reducing the thermal expansion coefficient. In the photosensitive glass according to this embodiment, the Al2O3 content is preferably 1 to 20%. An Al2O3 content of 1% or more increases the stability of the glass and suppresses deterioration due to weathering. The Al2O3 content is more preferably 2% or more, even more preferably 2.5% or more, still more preferably 3% or more, particularly preferably 3.5% or more, even more preferably 4% or more, and most preferably 5% or more. Furthermore, the Al2O3 content is preferably 20% or less. If the Al2O3 content is 20% or less, crystal precipitation from the glass can be maintained. The Al2O3 content is more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less.
[0033] In both the refractive index changing glass and the microfabricated glass, which are specific embodiments of the photosensitive glass of this embodiment, the preferred range of the Al2O3 content is the same as above.
[0034] B2O3 is a component that is effective in improving acid resistance and reducing the thermal expansion coefficient. In the photosensitive glass according to this embodiment, the B2O3 content is preferably 0 to 20%. The inclusion of B2O3 in the photosensitive glass according to this embodiment increases the stability of the glass and suppresses deterioration due to weathering. In micro-fabrication glass, suppressing etching of the glass has the effect of improving the pattern shape accuracy due to etching. The B2O3 content is more preferably 0.1% or more, even more preferably 0.3% or more, still more preferably 0.5% or more, particularly preferably 1% or more, even more preferably 2% or more, and most preferably 3% or more. Furthermore, the B2O3 content is preferably 20% or less. If the B2O3 content is 20% or less, variations in crystal precipitation characteristics due to phase separation can be suppressed. The B2O3 content is more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less.
[0035] In both the refractive index changing glass and the microfabricated glass, which are specific embodiments of the photosensitive glass of this embodiment, the preferred range of the B2O3 content is the same as above.
[0036] Li2O is a component that reduces the viscosity of glass and improves its meltability, but adding too much of it will excessively disrupt the silica network structure, reducing glass stability. In addition, in microfabrication glass, Li2O is a component that forms and precipitates lithium silicate crystals such as Li2SiO3 crystals and Li2Si2O5 crystals. The photosensitive glass according to this embodiment preferably contains 0 to 20% of Li2O. The inclusion of Li2O in the photosensitive glass according to this embodiment facilitates the formation of lithium silicate crystals and the stabilization of the precipitated crystal phase. The Li2O content is more preferably 3% or more, even more preferably 4% or more, even more preferably 5% or more, particularly preferably 7% or more, even more preferably 7.5% or more, and most preferably 8% or more. Furthermore, when the Li2O content is 20% or less, glass stability is maintained. The Li2O content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and even more preferably 15% or less.
[0037] In the refractive index changing glass, which is a specific embodiment of the photosensitive glass of this embodiment, the preferred range of the Li2O content is the same as above, except that to precipitate NaF crystals alone, the Li2O content is preferably 0 to 3%.
[0038] On the other hand, in micro-processed glass, the Li2O content is preferably 1 to 20%. In micro-processed glass, a Li2O content of 1% or more promotes lithium silicate crystal precipitation. In micro-processed glass, the Li2O content is more preferably 3% or more, even more preferably 4% or more, even more preferably 5% or more, particularly preferably 7% or more, even more preferably 7.5% or more, and most preferably 8% or more. In the microfabricated glass, the preferred upper limit of the Li2O content is the same as that of the refractive index changeable glass.
[0039] Na2O is a component that reduces the viscosity of glass and improves meltability, but adding too much of it will excessively disrupt the silica network structure, reducing glass stability. It is also a component that contributes to reducing dielectric loss when mixed with Li2O or K2O. In refractive index-changing glass, it is a component that forms and precipitates NaF crystals. In the photosensitive glass according to this embodiment, the Na2O content is preferably 0 to 20%. The inclusion of Na2O in the photosensitive glass according to this embodiment improves glass meltability, and in the presence of fluorine:F, NaF crystals are easily obtained, stabilizing the precipitated crystal phase. The Na2O content is more preferably 1% or more, even more preferably 2% or more, even more preferably 3% or more, particularly preferably 4% or more, even more preferably 5% or more, and most preferably 5.5% or more. Furthermore, if the Na2O content is 20% or less, glass stability is maintained and deterioration due to weathering can be suppressed. The Na2O content is more preferably 19% or less, further preferably 18% or less, and even more preferably 17% or less.
[0040] In the micro-fabricated glass, which is a specific embodiment of the photosensitive glass of this embodiment, the preferred range of the Na2O content is the same as above.
[0041] On the other hand, in refractive index variable glass, the Na2O content is preferably 1 to 20%. In refractive index variable glass, a Na2O content of 1% or more promotes precipitation of NaF crystals. In refractive index variable glass, the Na2O content is more preferably 5% or more, even more preferably 8% or more, even more preferably 10% or more, particularly preferably 12% or more, even more preferably 14% or more, and most preferably 15% or more. In the refractive index change type glass, the preferred upper limit of the Na2O content is the same as that in the microfabricated type glass.
[0042] K2O is a component that reduces the viscosity of glass and improves meltability, but adding too much of it excessively disrupts the silica network structure, reducing glass stability. It is also a component that contributes to reducing dielectric loss when added in combination with Li2O or Na2O. It is also a component that facilitates the precipitation of Li2SiO3 crystals in microfabrication-type photosensitive glass. In the photosensitive glass according to this embodiment, the K2O content is preferably 0 to 20%. The inclusion of K2O in the photosensitive glass according to this embodiment improves glass meltability. The K2O content is more preferably 1% or more, even more preferably 2% or more, even more preferably 3% or more, particularly preferably 4% or more, even more preferably 5% or more, and most preferably 6% or more. Furthermore, if the K2O content is 20% or less, glass stability is maintained and deterioration due to weathering can be suppressed. The K2O content is more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 11% or less, and most preferably 10% or less.
[0043] In both the refractive index changing glass and the microfabricated glass, which are specific embodiments of the photosensitive glass of this embodiment, the preferred range of the K2O content is the same as above.
[0044] ZnO is a component that increases the solubility of Ag2O. ZnO can also exhibit effects such as improving chemical durability and suppressing undesired reduction of silver. In the photosensitive glass according to this embodiment, the ZnO content is preferably 1 to 20%. When the photosensitive glass according to this embodiment contains 1% or more of ZnO, it can dissolve enough silver to exhibit sufficient photosensitivity for selective crystal precipitation. The ZnO content is more preferably 1.2% or more, even more preferably 1.4% or more, particularly preferably 1.5% or more, even more preferably 1.7% or more, and most preferably 1.8% or more. Furthermore, if the ZnO content is 20% or less, the deterioration of the crystallization tendency can be suppressed. The ZnO content is more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 11% or less, and most preferably 10% or less.
[0045] In both the refractive index changing glass and the microfabricated glass, which are specific aspects of the photosensitive glass of this embodiment, the preferred content of ZnO is the same as above.
[0046] Fluorine (F) is a component that precipitates NaF crystals and also improves the meltability of the glass. In the photosensitive glass according to this embodiment, the F content is preferably 0 to 5%. When the photosensitive glass according to this embodiment contains F, NaF crystals are easily obtained and the precipitated crystal phase tends to be stable. The F content is more preferably 0.5% or more, even more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, even more preferably 2.3% or more, and most preferably 2.5% or more. Furthermore, if the F content is 5% or less, devitrification during molding due to the tendency of excessive precipitation of NaF crystals can be suppressed. The F content is more preferably 4.5% or less, even more preferably 4% or less, and even more preferably 3.5% or less.
[0047] In particular, in a refractive index change glass, which is a specific embodiment of the photosensitive glass of this embodiment, the F content is preferably 0.1 to 5%. In a refractive index change glass, an F content of 0.1% or more can promote the tendency of NaF crystal precipitation. In a refractive index change glass, the F content is more preferably 0.5% or more, even more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, even more preferably 2.3% or more, and most preferably 2.5% or more. In the refractive index changing glass, the preferred upper limit of the F content is the same as above.
[0048] Furthermore, it is preferable that micro-processed glass, which is a specific embodiment of photosensitive glass, contains substantially no F. That is, the F content in the micro-processed glass is preferably 100 ppm or less.
[0049] Bromine (Br) is a component that promotes the dissolution of silver components into glass. Furthermore, in the coexistence of fluorine (F), it also has the effect of facilitating the precipitation of NaF crystals. In the photosensitive glass according to this embodiment, the Br content is preferably 0 to 5%. By including Br in the photosensitive glass according to this embodiment, NaF-based crystals are easily obtained and the precipitated crystal phase tends to be stable. The Br content is more preferably 0.1% or more, even more preferably 0.3% or more, even more preferably 0.5% or more, particularly preferably 0.7% or more, even more preferably 0.9% or more, and most preferably 0.95% or more. Furthermore, if the Br content is 5% or less, devitrification during molding due to the tendency of excessive precipitation of NaF crystals can be suppressed. The Br content is more preferably 4% or less, even more preferably 3.5% or less, even more preferably 3% or less, particularly preferably 2.5% or less, even more preferably 2.2% or less, and most preferably 2% or less.
[0050] In particular, in the refractive index change glass, which is a specific embodiment of the photosensitive glass of this embodiment, the Br content is preferably 0.1 to 5%. In the refractive index change glass, a Br content of 0.1% or more can promote the tendency of NaF crystal precipitation. In the refractive index change glass, the Br content is more preferably 0.3% or more, even more preferably 0.5% or more, even more preferably 0.7% or more, particularly preferably 0.9% or more, and even more preferably 0.95% or more. In the refractive index change glass, the preferred upper limit of the Br content is the same as above.
[0051] On the other hand, in the micro-processed glass, which is a specific embodiment of the photosensitive glass of this embodiment, Br may be substantially absent, i.e., the Br content in the micro-processed glass may be 100 ppm or less.
[0052] Sb2O3 is a thermally reducing component that reduces metal ions during heat treatment. + It plays a role in reducing ions. In the photosensitive glass according to this embodiment, the content of Sb2O3 is preferably 0 to 1.0%. By including Sb2O3, metal ion reduction during heat treatment can be stably carried out. The content of Sb2O3 is more preferably 0.05% or more, even more preferably 0.08% or more, even more preferably 0.1% or more, particularly preferably 0.13% or more, even more preferably 0.15% or more, and most preferably 0.18% or more. Furthermore, if the Sb2O3 content is 1.0% or less, coloration of the glass can be suppressed. The Sb2O3 content is more preferably 0.95% or less, even more preferably 0.9% or less, even more preferably 0.85% or less, particularly preferably 0.8% or less, even more preferably 0.75% or less, and most preferably 0.7% or less.
[0053] In the refractive index change glass, which is a specific embodiment of the photosensitive glass of this embodiment, the preferred range of the Sb2O3 content is the same as above.
[0054] On the other hand, in the micro-processed glass, which is a specific embodiment of the photosensitive glass of this embodiment, the Sb2O3 content is preferably 0.01 to 1.0%. In the micro-processed glass, when the Sb2O3 content is 0.01% or more, Ag is easily removed by heat treatment after exposure. + It can reduce ions and promote Ag colloid formation. In the microfabrication glass, the Sb2O3 content is more preferably 0.05% or more, even more preferably 0.08% or more, even more preferably 0.1% or more, particularly preferably 0.13% or more, even more preferably 0.15% or more, and most preferably 0.18% or more. In the microfabrication type glass, the preferred upper limit of the Sb2O3 content is the same as that of the refractive index change type glass.
[0055] Like Sb2O3, SnO2 is a thermally reducing component and reduces metal ions during heat treatment. + It plays a role in reducing ions. The coexistence of Sb2O3 further enhances the thermal reduction effect. In the photosensitive glass according to this embodiment, the SnO2 content is preferably 0 to 1.0%. The inclusion of SnO2 in the photosensitive glass according to this embodiment promotes the formation of Ag colloids by heat treatment after exposure. The SnO2 content is more preferably 0.001% or more, even more preferably 0.01% or more, even more preferably 0.02% or more, particularly preferably 0.03% or more, even more preferably 0.04% or more, and most preferably 0.05% or more. Furthermore, if the SnO2 content is 1.0% or less, there is no risk of the metal ion reducing effect becoming excessive, resulting in the formation of Ag colloids and other damage to the function of the photosensitive glass. The SnO2 content is more preferably 0.5% or less, even more preferably 0.4% or less, even more preferably 0.3% or less, particularly preferably 0.2% or less, even more preferably 0.15% or less, and most preferably 0.1% or less.
[0056] In both the refractive index changing glass and the microfabricated glass, which are specific embodiments of the photosensitive glass of this embodiment, the preferred content of SnO2 is the same as above.
[0057] The refractive index changing glass, which is a specific embodiment of the photosensitive glass of this embodiment, preferably satisfies the following composition. In mass percentage, SiO2: 20~80% Al2O3: 1-20% B2O3: 0-20% Li2O: 0-20% Na2O: 1-20% K2O: 0-20% ZnO: 1 to 20% F: 0.1 to 5% Br: 0.1 to 5% Ag2O: 0.001~0.5% CeO2: 0.001-0.5% Sb2O3: 0-1.0% SnO2: 0-1.0% Contains:
[0058] Furthermore, the microfabricated glass, which is another specific embodiment of the photosensitive glass of this embodiment, preferably satisfies the following composition. In mass percentage, SiO2: 20~80% Al2O3: 1-20% B2O3: 0-20% Li2O: 1-20% Na2O: 0-20% K2O: 0-20% ZnO: 1 to 20% Ag2O: 0.001~0.5% CeO2: 0.001-0.5% Sb2O3: 0.01-1.0% SnO2: 0-1.0% Contains:
[0059] The photosensitive glass according to this embodiment preferably contains substantially no Cr, Ni, V, Mn, or Co. That is, the contents of Cr, Ni, V, Mn, and Co may be 5 ppm or less. This is because Cr, Ni, V, Mn, and Co are coloring components, which can cause problems with transmittance, particularly in variable refractive index glass. Furthermore, Cr, V, Mn, and Co are coloring components that absorb UV light, which can cause problems in the formation of Ag colloids.
[0060] The photosensitive glass according to this embodiment may contain components other than those described above (hereinafter referred to as "other components"), provided that the effects of the present invention are not impaired. Examples of other components include RbO, CsO, MgO, CaO, SrO, BaO, PO, GeO, ScO, YO, LaO, PrO, NdO, PmO, SmO, EuO, GdO, TbO, DyO, HoO, TiO, FeO, ZrO, NbO, MoO, HfO, TaO, and WO. The total content of these components is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, particularly preferably 1% or less, even more preferably 0.5% or less, and most preferably 0.1% or less.
[0061] In the refractive index changing glass and the microfabricated glass, which are specific aspects of the photosensitive glass of this embodiment, the preferred contents of other components are the same as those described above.
[0062] <Method for manufacturing photosensitive glass> Next, a method for producing photosensitive glass according to this embodiment will be described. The method for producing photosensitive glass according to this embodiment includes heating a glass raw material containing a photosensitizer component to obtain molten glass (melting step), molding the molten glass into a desired shape (molding step), and slowly cooling the molded glass (slow cooling step), and also includes reducing the β-OH value of the photosensitive glass (β-OH value reducing step). Each step will be described below.
[0063] The melting step is a step of heating a glass raw material containing a photosensitizer component to obtain molten glass. The photosensitizer component is a component capable of generating nuclei that serve as starting points for crystal growth, thereby selectively crystallizing exposed areas. Examples of the photosensitizer component include the aforementioned AgO. AgO is preferred because it does not absorb light in the visible region, is easily dissolved in glass, and has low raw material costs.
[0064] Examples of glass raw materials include a homogeneous mixture of metal oxides, carbonates, sulfates, nitrates, glass cullet, etc., in the form of powder or granules of an appropriate particle size. Glass cullet is glass waste generated during glass manufacturing processes, etc.
[0065] The method for heating the glass raw materials is not particularly limited, but for example, a method in which the glass raw materials are placed in a platinum crucible and the platinum crucible is placed in an electric furnace to heat and melt them can be mentioned. The melting temperature may be any temperature that can melt the glass raw materials used, and may be, for example, 1400 to 1600° C., preferably 1450 to 1550° C. The melting time may be, for example, 1 to 120 hours, preferably 2 to 100 hours, depending on the melting scale (weight).
[0066] The molding step is a step of molding the molten glass obtained in the melting step into a desired shape. The glass can be molded, for example, by pouring the molten glass into a preheated mold and solidifying it into a desired shape. In this case, the glass can be molded into a plate, a tube, or the like by a down-draw method, a press method, or the like, or into a block, a column, or the like by billet molding, or into other desired shapes depending on the intended use using a molding die.
[0067] The slow cooling step is a step of slowly cooling the glass formed in the forming step to room temperature. In this embodiment, the slow cooling step is preferably performed so that the cooling rate from temperature T1 to temperature T2 is 1° C. / min or less, where T1 is the annealing point (Ap) and T2 is the strain point (Sp).
[0068] By performing slow cooling from temperature T1 to temperature T2 at a cooling rate of 1°C / min or less, thermal strain inside the glass can be eliminated and variations in crystal precipitation can be suppressed. The cooling rate from temperature T1 to temperature T2 is more preferably 0.9°C / min or less, even more preferably 0.7°C / min or less, and particularly preferably 0.5°C / min or less. From the viewpoint of suppressing glass devitrification during slow cooling, the cooling rate from temperature T1 to temperature T2 is preferably faster than 0.1°C / min, more preferably 0.15°C / min or higher, and even more preferably 0.2°C / min or higher.
[0069] In the manufacturing method of this embodiment, even when the temperature T1 is changed from the annealing point (Ap), it is preferable that the cooling rate from the temperature T1 to the temperature T2 satisfy the above range. In this case, the range of change of the temperature T1 may be from the annealing point (Ap) + 30°C to the annealing point (Ap) - 10°C. If the temperature is raised too high, the glass may crystallize. In the manufacturing method of this embodiment, even when the temperature T2 is changed from the strain point (Sp), it is preferable that the cooling rate from the temperature T1 to the temperature T2 satisfy the above range. In this case, the range in which the temperature T2 is changed may be any range lower than the strain point (Sp).
[0070] In the manufacturing method of this embodiment, reducing the β-OH value means reducing the water content in the glass. By including the step of reducing the β-OH value, the crystal precipitation temperature difference of the obtained photosensitive glass can be controlled, thereby obtaining a photosensitive glass that can be patterned with high precision. The step of reducing the β-OH value may be performed during the melting step, molding step, and slow cooling step, as described below.
[0071] The method for lowering the β-OH value is not particularly limited as long as it can reduce the amount of water in the glass, and for example, the following methods (1) to (5) can be applied. (1) The molten cullet ratio, calculated as mole weight, must be 10% or more. (2) The temperature during melting of the glass raw materials is set to 1400°C or higher. (3) Hydrates, hydroxides, and deliquescent / hygroscopic materials are not used as glass raw materials. (4) Melting is carried out using a resistance heating electric furnace. (5) Dry air is introduced into the melting furnace to control the dew point in the melting area.
[0072] In the above (1), by setting the molten cullet ratio to 10% or more in terms of molar weight, the cullet has been melted once and the moisture content derived from the raw materials has been reduced, so the β-OH value can be reduced compared to when only raw materials are used. The molten cullet ratio is more preferably 20% or more, even more preferably 30% or more, and particularly preferably 40% or more. Furthermore, from the viewpoint of adjusting the valence balance of metal ions in the molten glass, the molten cullet ratio is preferably 70% or less, more preferably 60% or less. Cullet refers to glass waste that contains only the desired components and can be combined with raw materials to produce a desired composition.
[0073] In the above (2), by setting the temperature during melting of the glass raw materials to 1400°C or higher, the vapor pressure of water in the glass is increased, volatilization is promoted, and the β-OH value can be reduced. The temperature during melting of the glass raw materials is more preferably 1450°C or higher, further preferably 1480°C or higher, and particularly preferably 1500°C or higher. Furthermore, if the temperature is too high, reduction of metal ions in the glass proceeds, which may result in the formation of Ag colloids and other problems that impair the function of the photosensitive glass. Therefore, the temperature during melting of the glass raw materials is preferably 1600°C or lower.
[0074] In the above (3), by not using hydrates, hydroxides, or deliquescent / hygroscopic raw materials, the water content in the glass raw materials can be reduced, and the β-OH value of the glass can be lowered. Examples of hydrates include penta-molecular borax (Na2B4O7 / 5H2O) and aluminum nitrate hydrate (Al(NO3)3 / 9H2O). Examples of hydroxides include aluminum hydroxide (Al(OH)3), sodium hydroxide (NaOH), and potassium hydroxide (KOH). Examples of deliquescent / hygroscopic raw materials include the above-mentioned sodium hydroxide, potassium hydroxide, and lithium nitrate (LiNO3).
[0075] In the above (4), the resistance heating electric furnace is an electric furnace that generates heat by passing electricity through a heating element such as molybdenum disilicide, and heats the space inside the furnace. Since moisture is not generated from the heat source as in, for example, a combustion heating furnace, the β-OH value can be reduced efficiently.
[0076] In the above (5), by supplying dry air into the melting furnace, the dew point of the melting atmosphere is lowered and the partial pressure of water is reduced, thereby reducing the β-OH value of the photosensitive glass that is finally obtained. The type of dry gas is not particularly limited, but any suitable gas such as oxygen, nitrogen, or air can be used. Furthermore, by controlling the dew point in the melting area, the moisture content in the glass raw materials can be controlled within an appropriate range. The dew point in the melting area is preferably within the range of -70 to 20°C. If the dew point in the melting area is 10°C or lower, it is easy to control the moisture content in the glass. Furthermore, if the dew point is 5°C or lower, it is easy to adjust the β-OH value of the final photosensitive glass to a range of 0.15 / mm. The dew point in the melting area is more preferably within the range of -70 to 0°C, and even more preferably -70 to -10°C. The dew point can be adjusted by supplying a dry gas into the melting area (melting atmosphere).
[0077] The step of reducing the β-OH value is preferably carried out so that the β-OH value of the resulting photosensitive glass is 0.20 / mm or less, more preferably 0.15 / mm or less, even more preferably 0.10 / mm or less, still more preferably 0.080 / mm or less, particularly preferably 0.060 / mm or less, and most preferably 0.050 / mm or less. From the viewpoint of the effectiveness of the β-OH reduction measures, the step is preferably carried out so that the β-OH value is 0.005 / mm or more.
[0078] <Application> The photosensitive glass according to this embodiment can form a highly accurate pattern when exposed to light and heat treated, making it suitable for use in optical elements and substrates for microfabrication. Examples of optical elements include volume holographic diffraction gratings, and examples of substrates for microfabrication include circuit boards for high-frequency applications and substrates for microfluidic devices.
[0079] In particular, the refractive index-changing glass according to a specific embodiment of the photosensitive glass of this embodiment can periodically change the refractive index of exposed and unexposed areas by two-beam interference exposure, and is particularly suitable for use as or is used as a volume holographic diffraction grating.
[0080] Furthermore, in the microfabricated glass according to another specific aspect of the photosensitive glass of this embodiment, a micropattern such as a glass through-hole (TGV) or a cavity can be formed by drawing a micropattern all at once using mask exposure and then etching after crystal precipitation. Therefore, the microfabricated glass can be suitably used particularly for circuit boards for high-frequency applications and substrates for microfluidic devices.
[0081] As described above, the present specification discloses the following configurations. 1. Photosensitive glass with a β-OH value of 0.20 / mm or less. 2. The cumulative light intensity at wavelengths of 280 to 360 nm is 2 J / cm 2 2. The photosensitive glass according to 1 above, wherein the difference between the crystal precipitation temperature after exposure to light so as to be equal to or greater than 10° C. and the crystal precipitation temperature before exposure is 10° C. or more. 3. Mass percentage: Ag2O: 0.001~5% CeO2: 0.001-5% 3. The photosensitive glass according to 1 or 2 above, comprising: 4. Mass percentage: SiO2: 20~80% Al2O3: 1-20% B2O3: 0-20% Li2O: 0-20% Na2O: 0-20% K2O: 0-20% ZnO: 1 to 20% F: 0-5% Br: 0-5% Ag2O: 0.001~0.5% CeO2: 0.001-0.5% Sb2O3: 0-1.0% SnO2: 0-1.0% 4. The photosensitive glass according to any one of 1 to 3 above, which contains: 5. The photosensitive glass according to any one of 1 to 4 above, which is substantially free of Cr, Ni, V, Mn and Co. 6. Heating a glass raw material containing a photosensitizer component to obtain molten glass; forming the molten glass into a desired shape; and annealing the molded glass, A method for producing a photosensitive glass, comprising reducing the β-OH value of the photosensitive glass. 7. The slow cooling is carried out so that the cooling rate from temperature T1 to temperature T2 is 1°C / min or less (the temperature T1 means the slow cooling point temperature, and the temperature T2 means the strain point temperature). 7. A method for producing photosensitive glass according to 6 above. [Example]
[0082] Examples will be described below, but the present invention is not limited to these Examples, in which Examples 1 to 14 are Examples and Example 15 is a Comparative Example.
[0083] <Preparation of photosensitive glass> (Examples 1 to 11: Variable refractive index glass) Glass cullet containing SiO2, Al(OH)3, NaCO3, NaF, NaBr, K2CO3, ZnO, CeO2, SnO, Sb2O3, and Ag was used as raw materials and placed in an 8-L platinum crucible. It was then heated and melted at 1500°C for 24 hours while stirring. The uniformly melted glass was poured into a cast iron mold, formed into a 20 mm thick plate, and slowly cooled to obtain the refractive index-changing glass for each example. Melting was performed in air and in an environment where dry air was introduced into the furnace, and the β-OH was adjusted for each example. The β-OH values for each example are shown in Table 1. Although the glass composition was the same for all examples 1 to 11, the compositions of easily volatile components such as F and Br varied from melt to melt, resulting in different glass compositions. (Examples 12-15: Microfabricated glass) Glass cullet containing SiO2, Li2CO3, NaCO3, K2CO3, Al(OH)3, BO3, ZnO, CeO2, Sb2O3, and Ag was used as raw materials. It was placed in an 8-L platinum crucible and heated to 1500°C under atmospheric stirring for 24 hours. The uniformly melted glass was poured into a cast iron mold, formed into a 20 mm thick plate, and slowly cooled to obtain the microfabricated glass shown in each example. The initial raw material was Al(OH)3, but this was changed to Al2O3, and the β-OH was adjusted for each example. The β-OH values for each example are shown in Table 1. Although the glass composition used in Examples 12 to 15 was the same, the compositions of easily volatile components such as F and Br varied from melt to melt, resulting in different glass compositions.
[0084] <Physical properties> (β-OH value) Using a Fourier transform infrared spectrophotometer (JASCO Corporation, model number: FT / IR-4100), -1 and 3845 cm -1 The absorbance of each sample was measured, and the β-OH value was calculated using the following formula. The β-OH values for each sample are shown in Table 1. β-OH value ( / mm) = (3570 cm -1 Absorbance of -3845cm -1 absorbance) / t t: thickness of glass sample (mm)
[0085] (Crystal precipitation temperature difference) The glass sample obtained above was crushed and measured using a differential thermal analyzer (Rigaku Thermoplus TG8120) and a differential scanning calorimeter (Rigaku ThermoPlusEVO2 DSC8271) under conditions of a sample weight of 30-60 mg and a heating rate of 10°C / min. Regarding the exothermic peak resulting from crystal precipitation under constant heating rate on the obtained chart, the extrapolated temperature of the inflection point at the start of heat generation was taken as the crystal precipitation temperature. The extrapolated temperature was taken as the temperature at the intersection of the extension of the portion without heat change before heat generation and the extension of the point where the gradient of the heat change after the start of heat generation is maximum. Next, the glass sample obtained above was irradiated with a photochemical mercury lamp (Toshiba Corporation: H-400P) at a wavelength of 280 to 360 nm with an integrated light intensity of 2 J / cm. 2 The exposure was carried out so that the above-mentioned value was achieved. The UV irradiance was measured using an ultraviolet integrating actinometer (Ushio Inc.: UIT-250) and a photodetector (Ushio Inc.: UVD-S313). After exposure, the crystallization temperature of the glass sample was measured in the same manner as above. The crystallization temperature difference was determined by subtracting the crystallization temperature after exposure from the crystallization temperature before exposure. The β-OH values for each example are shown in Table 1.
[0086] <Evaluation of microfabrication> The micro-machined glasses of Examples 14 and 15 were subjected to exposure and heat treatment under the following conditions to precipitate crystals, and then etched to evaluate their micro-machinability. A high-pressure mercury lamp (Ushio Inc.: ultra-high-pressure mercury lamp USH-250BY) was used, and the integrated light intensity at wavelengths of 280 to 360 nm was 2 J / cm. 2 The mask was exposed under the above conditions, then heat treated at 545°C for 10 hours to precipitate crystals, and then etched with a 10% HF aqueous solution. A micrograph of Example 14 after microfabrication is shown in FIG. 1(a), and a micrograph of Example 15 after microfabrication is shown in FIG. 1(b).
[0087] [Table 1]
[0088] From the examples of refractive index change glass in Examples 1 to 11, it was found that not only the composition but also the β-OH value is an influential factor in the crystal precipitation temperature difference. Furthermore, when the β-OH value was 0.20 / mm or less, the crystal precipitation temperature difference was 10°C or more, which was a good result. Furthermore, in the case of microfabrication glass, Examples 12 to 14, in which the β-OH value was 0.20 / mm or less, showed good results, with a crystal precipitation temperature difference of 10°C or more. On the other hand, Example 15, in which the β-OH value exceeded 0.20 / mm, showed a poor result, with a crystal precipitation temperature difference of less than 10°C. Furthermore, in the evaluation of microfabrication, Example 14 showed good microfabrication without etching defects in the exposed area A and the unexposed area B because the crystal precipitation temperature difference was 10°C or more, but Example 15 showed etching defects due to microcrystal precipitation in the unexposed area B because the crystal precipitation temperature difference was less than 10°C. This is thought to be because, during mask exposure, weak diffracted light is generated at the opening through which ultraviolet light passes. When the crystal precipitation temperature difference between the presence and absence of exposure is small, even weak diffracted light creates a crystal precipitation promotion effect due to photosensitivity, making it easier for microcrystals to precipitate in the unexposed area as well, resulting in a deterioration in the microfabrication shape due to etching.
Claims
1. A photosensitive glass having a β-OH value of 0.20 / mm or less.
2. The integrated light intensity at wavelengths of 280 to 360 nm is 2 J / cm 2 2. The photosensitive glass according to claim 1, wherein the difference between the crystal precipitation temperature after the exposure to light so as to be equal to or greater than 10[deg.] C. and the crystal precipitation temperature before the exposure to light is equal to or greater than 10[deg.] C.
3. In mass percentage, Aẹ 2 O:0.001~5% CeO 2 :0.001~5% The photosensitive glass according to claim 1 or 2, which contains
4. In mass percentage, Yes 2 :2~80% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :1~220% B 2 O 3 :0~20% Li 2 O:0~20% Na 2 O:0~20% K 2 O: 0~20% ZnO: 1 to 20% F: 0-5% Br: 0 to 5% Aẹ 2 O:0.001~0.5% CeO 2 :0.001~0.5% Sb 2 O 3 :0~1.0% SnO 2 :0~1.0% 3. The photosensitive glass according to claim 1, which contains
5. 3. The photosensitive glass according to claim 1, which is substantially free of Cr, Ni, V, Mn and Co.
6. Heating a glass raw material containing a photosensitizer component to obtain molten glass; forming the molten glass into a desired shape; and slowly cooling the molded glass, reducing the β-OH value of the photosensitive glass.
7. The slow cooling is performed so that the cooling rate from temperature T1 to temperature T2 is 1° C. / min or less (the temperature T1 means the slow cooling point temperature, and the temperature T2 means the strain point temperature). A method for producing the photosensitive glass according to claim 6.
Citation Information
Patent Citations
Sensitized photosensitive glass and manufacturing thereof
JP2017036200A